Hexahydric component metal organic frameworks constructed by multiple ligands and mixed-valence ions. Issue 9 (28th March 2022) - Li, Wen-Liang; Li, Tian-Ran; Du, Xin-Jie; Zhao, Jiong-Peng; Liu, Fu-Chen
Abstract : A six-component conductive MOF was synthesized by the self-assembly of metals and ligands, and the OER performance was greatly improved by metal replacement. Abstract : In this work, we report two multi-component MOFs [CH3 NH2 CH3 ]2 [FeIII2MII10(tz)11 (HCO2 )12 (btc)5/3 ] (MII10 = FeII10 for 1 and MII10 = FeII2CoII8 for 2 ) obtained by solvothermal reaction of benzene-1, 3, 5-tricarboxylate (btc) and 1, 2, 4 triazole (tz), Fe II and Fe III /Co II in DMF. In the complexes, several different types of metal rings (9, 12-number metal ions) are generated, and the connection of those rings gives the complicated three-dimensional structure. The two complexes exhibit electronic conductivity and good alkali stability, which makes them potential OER electrocatalysts. It is revealed that the cobalt ion greatly enhances the OER performance, and the electrode prepared using 2 shows a low overpotential of 339 mV at 10 mA cm −1 .